Sustainable Development Goals (SDGs) and Quality Education: Critical Analysis of Hadith - Salwa Dama Nazila; Ahlan Ahlan (Spiritus: Religious Studies and Education Journal, 2024)
Education is considered an important human right for all individuals. Research must be adapted to the social context of society and this is also the focus of the Sustainable Development Goals (SDGs), which emphasize the importance of quality education and supporting lifelong learning. Efforts to provide equal educational opportunities for all groups, regardless of gender, are recognized as an important step in advancing knowledge and supporting sustainable development. In this research, the library method is used to analyze various sources related to the SDGs, with the aim of supporting ongoing research efforts. The data collection technique used is documentation to verify the validity of the data, carry out interpretation and present concrete conclusions. Meanwhile, the data analysis technique is in the form of descriptive-analytical or context analytical, where researchers try to describe social phenomena that occur in the educational environment. Findings from research show that quality education is a key component in preparing future generations towards 2030. Based on the hadith, it states that to be able to achieve Quality education in realizing the SDGs requires an educational institution that is able to harmonize theory, practice and spirituality to balance the world and the hereafter. To achieve this, steps are needed to implement quality education, including; increasing access to education, quality of education and learning, adequate educational facilities, education financing, measurement and evaluation, lifelong education, and emphasis on education for sustainable development.